Metagenomics approach to unravel the potential of lignocellulosicresidues towards the discovery of novel enzymes - Santos, A. O. (2021)
Composting units which handle lignocellulosic residues are suitable sources of novel and promising lignocellulose-degrading enzymes such as cellulases, xylanases and laccases. These enzymes have practical application in biorefineries where lignocellulose is converted into several added-value bioproducts. However, the effective conversion of lignocellulose by a sustainable process is currently incomplete and there is a need to find novel and robust catalysts to overcome this fact. A function-based metagenomic approach was performed to identify novel lignocellulose-degrading enzymes. The DNA was extracted from compost samples and fosmid metagenomic libraries were constructed. A functional two-step screening was performed to select the most promising catalytic actions under extreme pH and temperature conditions.